Inside Front Cover: Intracellular aggregations of biological elements: From simple to complex. Issue 3 (29th June 2021) - Li, Fangzhou; Lan, Xinmiao; Liang, Xing‐Jie
Abstract : Organisms have evolved into orderly integrated systems. The complexes formed by the various components within the cell are essential for the execution of functions. There are three main forms of intracellular aggregates, namely protein‐protein complexes, protein‐nucleic acid complexes and protein‐nucleic acid‐lipids complexes, which are of great importance for research. (Article number 2021, 2, e27 )